Pengaruh Financial Distress dan Konservatisme Akuntansi pada Tax Avoidance - Swandewi, Ni Putu; Noviari, Naniek (E-Jurnal Akuntansi; Vol 30 No 7 (2020)DO - 10.24843/EJA.2020.v30.i07.p05, 2020)
Tax avoidance can be interpreted as an effort to avoid tax that is done in a legal and safe way for taxpayers because it does not conflict with applicable tax laws. This study aims to empirically examine the effect of financial distress and accounting conservatism on tax avoidance which is proxied by using a cash effective tax rate (CETR). The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018 totaling 168 companies. The sample used was 44 companies with a total observation sample of 176 in 4 years. Data analysis technique used in this study is multiple linear regression analysis techniques. Based on the analysis, it was found that the financial distress variable had a significant positive effect on tax avoidance, and accounting conservatism had a significant negative effect on tax avoidance. Keywords: Financial Distress; Accounting Conservatism; Tax Avoidance.